“Gaidar remains in formation today...” (on the canon of Soviet children’s reading and cultural recycling) - S. G. Maslinskaya (Шаги, 2024)
The article is devoted to the problem of demand and concomitant reinterpretation of the Soviet literary heritage in the 2000s. The work of Arkady Gaidar, recognized as the best Soviet children’s writer during his lifetime and as an author who fully expressed Soviet values — heroism in the struggle for the establishment of Soviet power and collectivism — in the Soviet period was widely available to readers-children. Both the print runs of his works and the number of reprints (including in school anthologies) were very significant: he was in the top ten in terms of the size of print runs and the regularity of reprints. Based on a study of the history of the publication of Gaidar’s texts from 1926 to 1984, publishing and pedagogical preferences in the selection of works for reprinting have been identified: most often, “The Tale of a Military Secret” was reprinted in impressive numbers, as its ideological content glorified heroic sacrifice in the name of establishing Soviet power. The story “Timur and His Gang” had the same number of reissues as “Military Secret”. In the 1990s, reprinting of Gaidar’s works was sharply reduced, and the choice of what was published also changed: the first place is occupied by “Chuk and Gek”, which depicted everyday family life. In 2000–2022, the story “Timur and His Gang”, which emphasizes the values of class mutual assistance and collectivism, becomes the most reprinted. Publication of other works by Gaidar also demonstrates a noticeable change in emphasis: there is a sharp drop in reissues of the stories “School” and “R. V. S.”, which have temporal contextualization in the historical events of the October Revolution and the Civil War. This allows us to say that the mobilization narrative, which is generally characteristic of Gaidar’s works, is losing its historical conditionality (the Revolution and the Civil War). At the same time, the reprinting of works about peacetime, which takes place in the immediate vicinity of hostilities that require mobilization efforts by both adults and children, have been renewed in the current book offerings for young readers. Recent initiatives to bring Gaidar’s works back into the school curriculum also testify to the reactualization.